2020
DOI: 10.1186/s12886-020-01492-z
|View full text |Cite
|
Sign up to set email alerts
|

Cataract and glaucoma combined surgery: XEN® gel stent versus nonpenetrating deep sclerectomy, a pilot study

Abstract: Background: To compare the efficacy of phacoemulsification (PKE) combined with nonpenetrating deep sclerectomy (NPDS) with mitomycin C (MMC) versus XEN® gel stent with MMC. Methods: In this nonrandomized, retrospective, comparative, single-center pilot study, 105 consecutive eyes of 75 patients with uncontrolled primary open-angle glaucoma (POAG) and cataract who underwent PKE combined with either XEN implantation (n = 47) or NPDS (n = 58) between May 2013 and November 2018 were included. The primary outcome w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 32 publications
4
22
1
Order By: Relevance
“…To date, cost-effectiveness evidence for the XEN gel stent is not available (89), which will be the main consideration that will definitely affect the acceptance of new surgical procedures. Theillac et al (48) suggested that compared with the traditional filtration surgery, XEN implantation could reduce operation time, which could be used to perform other surgical procedures, and offset the additional cost. Marques et al (90) and Busch et al (60) intended to evaluate the learning curve of XEN gel stents with several surgeons from different professional fields.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, cost-effectiveness evidence for the XEN gel stent is not available (89), which will be the main consideration that will definitely affect the acceptance of new surgical procedures. Theillac et al (48) suggested that compared with the traditional filtration surgery, XEN implantation could reduce operation time, which could be used to perform other surgical procedures, and offset the additional cost. Marques et al (90) and Busch et al (60) intended to evaluate the learning curve of XEN gel stents with several surgeons from different professional fields.…”
Section: Discussionmentioning
confidence: 99%
“…In another study comparing XEN implantation and EX-PRESS drainage device implantation (15), EX-PRESS showed superiority in terms of success rate although XEN implantation could reduce the risk of hypotony and choroidal effusion with fewer postoperative clinical visits. In another 9-month followup study, non-penetrating deep sclerectomy (NPDS) with MMC was compared with XEN gel stent implantation with MMC (48). The mean reduction in IOP between baseline and the last follow-up was −18.9 ± 5.2% and −25.6 ± 4.3% in the XEN and NPDS groups, respectively (p = 0.39).…”
Section: Comparison With Other Surgeriesmentioning
confidence: 99%
“…A recent nonrandomized retrospective monocentric study compared both procedures combined with cataract surgery without demonstrating any difference in the risk of success or safety profile. 18 However, the short followup may not have revealed a real difference. A total of 328 eyes of 282 consecutive glaucomatous patients over 18 and scheduled for standalone XEN implantations (n = 140) or NPDS (n = 188) in our institution were assessed for eligibility.…”
mentioning
confidence: 99%
“…The weighted mean Forty-five studies (n = 3122 total eyes) reported 12-month outcomes with complete pre-and postoperative IOP and medication use. 4,5,[10][11][12]15,19,20,25,[27][28][29][30][31][32][33][35][36][37][38][39][40][42][43][44][45][46][47][48][51][52][53]55,[57][58][59][60][62][63][64][65][66][67][68] In these studies, the median number of eyes followed was 52 (range, 12-242) and median age was 72.2 years (range, 53.4-80.9). The weighted mean preoperative IOP was 22.2 mm Hg on 2.5 glaucoma medications, and the weighted mean postoperative IOP was 14.2 mm Hg on 0.7 glaucoma medications.…”
Section: Efficacy Outcomesmentioning
confidence: 97%